Pencarian Pom Bensin Terdekat di Denpasar Menggunakan Algoritma Djikstra Berbasis Web Mobile - Putu Andhika Kurniawijaya (Jurnal Teknologi Informasi dan Komputer, 2015)
Denpasar as one of travel destination in Indonesia, is often visited by local and foreign tourists. Even some of those tourist who traveled in Denpasar is unaccompanied by a guide. Regional and environmental differences could be   problems for tourists who do not recognize Denpasar areas very well. They are confused to find gas stations when needed.The author uses Dijkstra's algorithm method,which purpose is to determine nearest gas station to the tourists. The initial step in this method is to give the weight value (distance) from one point to another point, then gives a value of 0 at the starting point and infinite value to the other point. From the point of departure, the algorithm compare the unidentified neighboring point and count the distance from the point of departure.The smallest value of the destination point is the smallest weight of the starting point to the point of destination. By using J2ME search results layout nearest gas station can be displayed on a mobile traveler.Based on the analysis of several trials of the method of Dijkstra's algorithm, it can be determined that the method can provide the right solution in the search for the nearest gas station because it can provide quick results according to the needs of travelers. In addition, the search results can be displayed on mobile travelers, making it easier to search.Keywords : Djikstra’s Algorythm, Web Mobile.